Pengajaran Pendidikan Jasmani dan Perkembangan Gerak - Bambang Abduljabar (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
The Instruction of physical education is closely associated with the motiondevelopment as continuum changes in the motion behavior along human life that arehappened through interactions between characteristics of the task of motion, individualbiological factors, and the local environmental conditions.A study of the human motion development is often seen from various categories leading to imbalances of the developmental process, that is at the domains (cognitive, affective, psychomotor), or the interrelation of behavioral-age (under five-year-old, child,adolescent, adult, middle age, old), or from a biological view, in the environment andperspective of the task of motion. The concept of the motion development itself is learned through three ways that are: longitudinal, cross-sectional and mixed-longitudinalstudy. The stages of the motion development can be classified into various means thatare: age chronology (biological age, morphological age, age of skeleton’s growth, toothage, sexual age, emotional age, mental age, age of self-conception, and perceptual age).Teachers of the physical education are required to instill the concept of motion to allstudents and not to forget the important factor “move as an important characteristic oflife”. The appliance of the physical education at school or in informal condition shouldbe able to lead all students to master their own skills in maintaining and improving theirmotion ability. To a further implication, the application of the conventions of the motiondevelopment into the instruction of the physical education needs a clear distinctionbetween the Elementary School, Junior High School, and Senior High School. Thatdistinction is good at the target orientation, material, and its process of learning.Keywords: Motion development and physical education